Evaluation of a New Oncogynecologic Training Program. Issue 7 (1st September 2016) - Tuncer, Hasan Aykut; Ozgul, Nejat; Kuscu, Esra; Dursun, Polat; Ayhan, Ali
Abstract : Objective: The first cohort of Turkish fellows has begun to graduate from a newly accredited training program on gynecologic oncology. This study aimed to investigate the value of experience on the confidence of these fellows to perform surgical procedures. Methods: We assessed the characteristics of 32 fellows, including the perceived adequacy of their fellowship training, the facilities of the clinics at which they were trained, and their levels of exposure and confidence in performing a total of 44 procedures. Exposure levels were performing, assisting with, observing, or no exposure. Confidence was assessed by asking whether they could perform each procedure. Correlation analysis was used to determine the link between exposure levels and confidence. Results: The confidence of fellows to perform a surgical procedure increased with exposure to that procedure ( r = 0.820, P < 0.001). Performing, assisting with, and observing a procedure created a sense of confidence in 97.2%, 54.1%, and 31.1% of fellows. The majority of fellows (>75%) had performed type 2 hysterectomy, total omentectomy, and pelvic and para-aortic lymphadenectomy. None of the fellows had ever performed a trachelectomy. Conclusions: Efforts should be made in accredited systems for gynecologic oncology surgical training to provide more opportunities for trainees to perform surgical procedures, rather than assisting with and observing them.